Accelerated growth and structural transformation: Assessing Ghana’s options to reach middle-income status - Breisinger, Clemens; Diao, Xinshen; Thurlow, James; Yu, Bingxin; Kolavalli, Shashidhara (International Food Policy Research Institute, 2007)
Ghana has made considerable progress over the last 20 years in sustaining economic growth and reducing poverty. The Government of Ghana has declared its new development goal of reaching middle-income status by 2015. Achieving this goal will require Ghana to double its per capita income over the next decade. In this paper we explore the growth experiences of other developing countries that have successfully transformed their economies from situations similar to Ghana’s today. Based on the past experiences of these fast growing countries, and using a dynamic general equilibrium model developed for Ghana, we evaluate sources of accelerated growth and their contributions to overall growth and transformation... The authors conclude that, for Ghana to reach middle-income status it will require careful coordination between increasingly complex macroeconomic, industrial and financial market policies, which also require the improvement of institutional capacity of the government to implement such complex policies.